ENTREPRENEURSHIP MANAGEMENT AT PRIMARY SCHOOL - Nur Indah Lailya Mawar Sari; Syahrul Nursianawati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This article aims to describe the importance of entrepreneurship at primary schools. This form of research is descriptive qualitative. Data collection using observation sheets and interviews. The data obtained were collected and processed using qualitative analysis techniques. the results of this study indicate that the need for entrepreneurial management in primary schools to create independent and creative schoolchildren. In entrepreneurship at primary schools it is necessary to work together for the achievement of goals. The development of entrepreneurship management needs to perform the functions of planning, organizing, implementing, and controlling or supervising.